Parental acceptance of novel children's medical syringes and their influencing factors - Luo, Su Wen; Yang, Peng Rui (Frontiers in Psychology, 2025)
BackgroundWith the rising global demand for medical syringes among children, the unsuitability of traditional syringes may negatively affect their physical and mental health.MethodsThis study integrates the extended Technology Acceptance Model (TAM) to survey 455 child guardians on 10 variables influencing their attitudes toward pediatric medical syringes.ResultsResults indicate that aesthetic preferences of users significantly influence the price value sensitivity and purchasing decisions of children's guardians. Furthermore, the product's function and price value significantly shape users' behavioral intentions. Technology anxiety and time and error reduction emerge as key factors influencing perceived risks.ConclusionsThis study offers product designers crucial insights into purchasing factors for children's medical products, aims to enhance product development and iteration efficiency, and promotes more accurate innovation, decision-making, and communication. Additionally, it proposes new recommendations for ethical and marketing strategies.